Correlation between Serum 25-Hydroxy Vitamin D levels and the severity of acne vulgaris: A systematic review - Shinta D Rasti; Nena R Dewinta; Ronik H Kamal; Avina F Adissadah; Afhama E Madanny; Linda Dewanti (Wolters Kluwer Medknow Publications, 2022)
Background: Vitamin D is thought to play a role in the pathogenesis of acne, and its levels can change in patients with acne vulgaris. Several studies have revealed that serum 25-hydroxy vitamin D levels tend to be low and statistically significant in acne vulgaris patients. However, the relationship between vitamin D levels and acne severity is still poorly understood. Objective: This study aims to identify the correlation between serum 25-hydroxy vitamin D levels and the severity of acne vulgaris. Method: This systematic review study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline based on several studies taken from the PubMed, PMC, Semantic Scholar, and ResearchGate databases until June 2021. Full-text case-control, randomized controlled trial, or cross-sectional study in English or Indonesian language reporting on the serum 25-hydroxy vitamin D levels and the severity of acne vulgaris on human participants were included. Result: From a total of 401 studies, 10 studies met the criteria. Almost all studies (8 of 10) revealed lower serum 25-hydroxy vitamin D levels as the acne severity progresses, although 2 of them were not statistically significant. Conclusion: The evidence of an inverse correlation between serum 25-hydroxy vitamin D levels and the severity of acne vulgaris suggests the need for screening of vitamin D levels in acne patients and offers a new prospect in the field of acne prevention and treatment.